Persepsi Guru Terhadap Gerakan Literasi Sekolah Di Madrasah Aliyah Negeri (MAN) 1 Banjarmasin - Arliani Arliani; Rochgiyanti Rochgiyanti; Sriwati Sriwati (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
The School Literacy Movement (GLS) is a government program that involves reading non-textbooks for 15 minutes before learning begins. Teacher participation is needed to encourage the implementation of activities to run smoothly. As supervisors of implementing activities, teachers can undoubtedly understand the conditions for implementing activities well, so it is essential to know the teachers' perceptions. This research analyses teachers' perceptions of implementing GLS at MAN 1 Banjarmasin. The research method used is descriptive qualitative. Data collection is done through observation, interviews, and document study. Data analysis techniques use Miles and Huberman references: data collection, data reduction, data presentation, and conclusion. This research shows that teacher perceptions can be seen from the teacher's understanding of the implementation of GLS and students' literacy skills. It can be concluded that teachers' perceptions of GLS can vary depending on influencing factors. Teachers are expected to be able to provide encouragement and support through innovation to increase students' interest in reading and literacy skills.